Translation of Arabic Polysemy in the Holy Quran: A Comparative Analysis - Kembaren, Farida Repelita Waty; Daulay, Ernita; Lubis, M. Husnan; Siregar, Rizqia Fitri (SCOPE: Journal of English Language Teaching, 2024)
This study aims to analyze the translation of polysemy in the Qur'an, focusing on comparing different versions of the translation. Polysemy, which refers to a single word with multiple meanings, often poses challenges in translating sacred texts such as the Qur'an, where accuracy and context are crucial. This study used a qualitative method with a descriptive qualitative research design to evaluate how translators differ in interpreting and translating polysemy words from Arabic into Batak Angkola, Indonesian, and English. Batak Angkola language is one of the regional languages mainly spoken in the southern Tapanuli region. Batak Angkola was chosen because it is rarely used, especially for the younger generation who do not live in the area. Batak Angkola language translation of the Qur'an can make it easier, especially for those who are still limited in vocabulary, to better understand the translation of Qur'an and can be a reference for the future. In the analysis section, the five Arabic polysemies studied were collected and analyzed based on Katz and Fodor's theory of meaning component analysis. The findings of this study show that there are significant variations in the translation approaches used by translators, which affect the understanding and interpretation of the meaning of Qur'an verses. The article also underlines the importance of understanding the historical and linguistic contexts in the translation process so that the resulting meaning can remain consistent with the original text.